Ultrafast Transmission Electron Microscopy: Techniques and Applications. (September 2021) - Montgomery, Eric; Leonhardt, Darrin; Roehling, John
Abstract : Abstract: With the growing applications of temporally resolved electron microscopy for probing basic phenomena and reducing beam-induced damage, a multifaceted introduction to the field of ultrafast transmission electron microscopy is provided. This primer includes techniques and equipment as well as implementation perspectives. Historical developments and recent technical advances will provide insight into ultrafast capabilities for research as well as educate electron microscopists on the general techniques. This technology review also includes applications enabled by ultrafast techniques using various sample stimuli from multidisciplinary fields.